Effect of Multi-channel Functional Electrical Stimulation on Cognitive Function of Bedridden Elderly - Dandan XIE; Yulian REN; Cheng CHEN; Chen ZHANG; Xiaokuo HE (康复学报)
Objective:To explore the effect of multi-channel functional electrical stimulation (FES) on the cognitive function of bedridden elderly, and observe its effect on the complications due to long-term bed, such as pulmonary infection, urinary tract infection and pressure sores.Methods:76 bedridden elderly were randomly assigned to the FES group (n=38) and control group (n=38). Both groups received routine treatment and basic nursing. The FES group was added with multi-channel FES for two weeks, once a day and five times each week. Before and after treatment, the Montreal cognitive assessment (MoCA) scores and event related potentials P300 were used to evaluate the cognitive function, modified Barthel index (MBI) was used to evaluate the activities of daily living (ADL), and the complications, such as pulmonary infection, urinary tract infection and pressure sores were evaluated.Results:After two weeks, the MoCA score and MBI score in both groups were significantly increased than those before the treatment (P<0.05), and the latency of event related potentials P300 was significantly shorter than that before the treatment (P<0.05). The incidence of pulmonary infection and urinary tract infection in FES group were lower than those of control group after two weeks (P<0.05).Conclusion:FES can improve the cognitive function of bedridden elderly effectively, increase the ADL ability and quality of life, reduce the incidence of long-term bedridden complications.